2022
DOI: 10.13057/biodiv/d231101
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and use of traditional medicinal plant species in Bantimurung-Bulusaraung National Park, Indonesia

Abstract: Abstract. Husaini IPA, Maulany RI, Nasri N, Ngakan PO. 2022. Diversity and use of traditional medicinal plant species in Bantimurung-Bulusaraung National Park, Indonesia. Biodiversitas 23: 5539-5550. The people of Minasatene (Pangkep District) in Bantimurung-Bulusaraung National Park, South Sulawesi (Indonesia) have used traditional medicinal plants for many centuries. However, this local knowledge has not been recorded. This study aims to examine the diversity of plant species used to treat various ailments i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…The administration route of medicinal plant preparations is primarily oral (81%), although a smaller proportion involves vaginal, topical, optical, and nasal applications as well (Figure 2C). Interestingly, our findings regarding the methods of preparation, routes of administration, and utilized plant parts are in close alignment with the results of prior investigations conducted in other Indonesian national parks (Susiarti et al 2018;Susanti and Zuhud 2019;Husaini et al 2022).…”
Section: Plant Part Used Preparation and Administration Routesupporting
confidence: 90%
See 1 more Smart Citation
“…The administration route of medicinal plant preparations is primarily oral (81%), although a smaller proportion involves vaginal, topical, optical, and nasal applications as well (Figure 2C). Interestingly, our findings regarding the methods of preparation, routes of administration, and utilized plant parts are in close alignment with the results of prior investigations conducted in other Indonesian national parks (Susiarti et al 2018;Susanti and Zuhud 2019;Husaini et al 2022).…”
Section: Plant Part Used Preparation and Administration Routesupporting
confidence: 90%
“…In Sumatra, Elliott and Brimacombe (1987) initiated such studies in Gunung Leuser, followed by Setyowati and Wardah (2007) documenting medicinal plants in Bukit Tigapuluh while Yudiyanto et al (2022) conducted ethno-pharmacological studies on the Lampung Tribe residing near Way Kambas National Park. Two ethnopharmacological studies were conducted on Sulawesi Island, specifically in Bantimurung-Bulusaruang (Husaini et al 2022) and Lore-Lindu (Gailea et al 2016). In Kalimantan, Susanti and Zuhud (2019) focused on traditional knowledge and the conservation of medicinal plants among the Dayak Krayan people in Kayan Mentarang National Park. In Java, within Meru Betiri National Park, studies have examined the various interests and influences of actors involved in the utilization of medicinal plants (Nurrochmat et al 2017), as well as revealing the pharmacological potential and phytochemical components of several medicinal plants (Nugraha et al 2020;Ratnadewi et al 2020), meanwhile Susiarti et al (2018) analyzed the diversity of medicinal plants in Mount Gede Pangrango, while Arbiastutie et al (2017) uncovered the anti-cancer potential of medicinal plants within this national park.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the 2017 Research on Medicinal Plants and Herbs, Indonesia has biological natural resources consisting of 2,848 species of medicinal plants with 32,014 medicinal herbs [ 2 ]. Husaini et al discovered 74 plant species in Bantimurung-Bulusaraung National Park, effective as herbal medicine in treating 54 ailments [ 3 ]. The Basic Health Research results from 2010 to 2018 also showed that the user of traditional health providers had increased to 44.3% [ 2 ].…”
Section: Introductionmentioning
confidence: 99%